2017
DOI: 10.1074/jbc.m117.788596
|View full text |Cite
|
Sign up to set email alerts
|

Commensal microbiota-induced microRNA modulates intestinal epithelial permeability through the small GTPase ARF4

Abstract: The intestinal tract contains many commensal bacteria that modulate various physiological host functions. Dysbiosis of commensal bacteria triggers dysfunction of the intestinal epithelial barrier, leading to the induction or aggravation of intestinal inflammation. To elucidate whether microRNA plays a role in commensal microbiome-dependent intestinal epithelial barrier regulation, we compared transcripts in intestinal epithelial cells (IECs) from conventional and germ-free mice and found that commensal bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 33 publications
0
79
0
Order By: Relevance
“…Other studies have examined intestinal epithelial cells directly to ensure that the observed miRNA differences were caused by the effect of gut microbes on epithelial cells alone. Using microarray and qPCR data, Nakata and colleagues [112] showed that miR-21-5p is expressed at higher levels in the small and large intestines of conventional mice than in germ-free mice. They then went on to show that exposing HT-29 and SW480 cells (two CRC cell lines) to heat-killed Bacteroides acidifaciens type A43 and to Lactobacillus johnsonii 129 resulted in an upregulation of miR-21-5p, suggesting that molecules derived from these bacteria (and not live bacteria alone) can directly regulate the expression of this well-studied oncomiRNA [112].…”
Section: The Gut Microbiome and Non-coding Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have examined intestinal epithelial cells directly to ensure that the observed miRNA differences were caused by the effect of gut microbes on epithelial cells alone. Using microarray and qPCR data, Nakata and colleagues [112] showed that miR-21-5p is expressed at higher levels in the small and large intestines of conventional mice than in germ-free mice. They then went on to show that exposing HT-29 and SW480 cells (two CRC cell lines) to heat-killed Bacteroides acidifaciens type A43 and to Lactobacillus johnsonii 129 resulted in an upregulation of miR-21-5p, suggesting that molecules derived from these bacteria (and not live bacteria alone) can directly regulate the expression of this well-studied oncomiRNA [112].…”
Section: The Gut Microbiome and Non-coding Rnasmentioning
confidence: 99%
“…Using microarray and qPCR data, Nakata and colleagues [112] showed that miR-21-5p is expressed at higher levels in the small and large intestines of conventional mice than in germ-free mice. They then went on to show that exposing HT-29 and SW480 cells (two CRC cell lines) to heat-killed Bacteroides acidifaciens type A43 and to Lactobacillus johnsonii 129 resulted in an upregulation of miR-21-5p, suggesting that molecules derived from these bacteria (and not live bacteria alone) can directly regulate the expression of this well-studied oncomiRNA [112]. Paradoxically, both of these bacteria are regarded as probiotic bacteria and not oncogenic [113,114], again indicating the need for studies focused on functional outcomes.…”
Section: The Gut Microbiome and Non-coding Rnasmentioning
confidence: 99%
“…However, we could not nd in the literature evidences of association between this miRNA and gut microbiota. implications in the regulation of intestinal epithelial permeability (Nakata et al, 2017). Otherwise, miR-130b-3p was only correlated with B. eggerthi abundance and there is evidence that the expression of this miRNA was in uenced by microbial status in intestinal epithelial stem cell of conventionalized mice compared to germ-free mice (Peck et al, 2017), showing that the miRNAs expression could be modulated by gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the gut microbiota regulates miRNA expression in IECs subtypes, and this regulation may alter intestinal homeostasis (Nakata et al, 2017). In this sense, it was demonstrated that the expression of some miRNAs is different among IEC subtypes and the difference depends on microbial patterns (Peck et al, 2017).…”
mentioning
confidence: 99%
“…Wild-type (WT) and MyD88 2/2 BALB/c mice were purchased from CLEA Japan (Tokyo, Japan) and Oriental BioService (Kyoto, Japan), respectively. Mice were bred under conventional (CV) or germ-free (GF) conditions as described previously (24). Female mice were used at 9-13 wk of age.…”
Section: Micementioning
confidence: 99%